Six-Month DAPT Noninferior to 12-Month Regimen following Stent Implantation - Hoyle, Brian (MD Conference Express, 2014)
Results from the Second Generation Drug-Eluting Stents Implantation Followed by Six Versus Twelve Month Dual Antiplatelet Therapy trial [SECURITY; Colombo A et al. J Am Coll Cardiol. 2014. In press] have demonstrated the noninferiority of postprocedural dual antiplatelet therapy for 6 months as compared with 12 months in non-high-risk patients undergoing percutaneous coronary intervention with a second-generation drug eluting stent.